The vesicular forebrain (pseudo-aprosencephaly): a missing link in the teratogenetic spectrum of the defective brain anlage and its discrimination from aprosencephaly - Sergi, Consolato M.; Schmitt, Horst Peter (Acta neuropathologica, 2000)
Two cases out of a sample of 41 fetuses and infants with prosencephalic malformation, observed at the Institute of Pathology and Department of Neuropathology of the University of Heidelberg, are described here in detail. These cases presented grossly with microcephaly and missing forebrain, appearing to be cases of aprosencephaly. However, in one of these cases glio-mesenchymal membranes with an ependymal outline, consistent with the microscopic appearance of the dorsal sac membrane in holoprosencephaly and obviously representing remnants of a collapsed primitive prosencephalic vesicle, could be demonstrated. In the other case only hindbrain structures, with the exception of the cerebellum, were present without any demonstrable remnants of a prosencephalon. We propose that the microscopic specification of a primitive prosencephalic vesicle in the first case and similar cases does not justify the diagnosis of atelencephaly/aprosencephaly because the prosencephalon was not really missing (pseudo-aprosencephaly). The prosencephalic anlage had been formed but remained vesicular without further differentiation of a holospheric brain mantle as in common holoprosencephaly ('vesicular forebrain'). We believe that pseudo-aprosencephaly represents the most primitive form of holoprosencephaly, in which the forebrain remains as a complete sac, linking classical holoprosencephaly with 'true' aprosencephaly, i.e., defective prosencephalic anlage due to developmental arrest. The 'vesicular forebrain' allows one to extend the classification of Probst by an additional category which might be termed complete sac category, intercalated between the dorsal sac category and 'true' atelencephaly/aprosencephaly.
Gesehen am 27.11.2017